Pheochromocytoma in a Postpartum Patient With Cardiogenic Shock From Epicardial Vasospasm Necessitating Mechanical Circulatory Support - Justin Brilliant; Sarah Leventhal; Mark Vesely; Brian Barr; Manjula Ananthram (Annals of Internal Medicine: Clinical Cases)
A 25-year-old woman presented with pheochromocytoma crisis and cardiogenic shock. Her ejection fraction was severely reduced at 10%, and she needed venoarterial extracorporeal membrane oxygenation (VA-ECMO) for hemodynamic support. Coronary angiography demonstrated diffuse coronary vasospasm as the underlying mechanism for her cardiogenic shock. Her ejection fraction improved with nondihydropyridine calcium channel blockers for treatment of epicardial coronary vasospasm. Her adrenal crisis was treated with sequential use of alpha-blockers followed by beta-blockers after resolution of cardiogenic shock; a right adrenalectomy was then performed before discharge. This case highlights the importance of prompt diagnosis and treatment of a pheochromocytoma complicated by cardiogenic shock when mechanical circulatory support is essential.